HOW DO CHILDREN WITH CEREBRAL PALSY (CP) AND DEVELOPMENTAL LANGUAGE DISORDER (DLD) MANIPULATE THEIR LANGUAGE? A CASE STUDY ON LANGUAGE COMPREHENSION - Afni Afifah Salsabilla; Emy Sudarwati (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study explores the differences and similarities in language comprehension and expressive abilities among children with Cerebral Palsy (CP) and Developmental Language Disorder (DLD). While the two disorders impact speech and language, their causes are rather different; CP results from motor impairment, while DLD results from impaired language processing. Through the use of a qualitative case study, two children, one with CP and the other with DLD, are used to examine their communication strategies, speech production, and language output. Data were collected through video observation of fluency, articulation, syntax, and coherence. The study indicates that a child with CP shows primarily expressive language impairment due to motor constraints, with well-maintained grammar and strong receptive capabilities despite slurred and late speech. Conversely, a child with DLD speech is fluent but disorganized, with pervasive grammatical errors and lexical difficulties, suggesting linguistic planning instead of motor impairments. Therapies, therefore, differ: CP therapy focuses on motor-based strategies like articulation and regulation of breathing, while DLD therapy targets the facilitation of grammar, vocabulary, and sentence formation by language-based activities like role play and storytelling. The study emphasizes the importance of tailored intervention, noting that therapy must be tailored to each child's unique language profile. It also emphasizes the relationship between language and Theory of Mind (ToM), suggesting that therapy for both conditions includes scope for the expression of thoughts and feelings. These findings shape a better view of speech-language disorders, improving diagnostic methods and treatment interventions for children with CP and DLD.